Work Accident Risk Analysis Using the HIRADC Method for Container Loading and Unloading Workers at PT Pelabuhan Indonesia (Pelindo) 1 Dumai in 2023 - AULIA PUTRI; YEYEN GUMAYESTY; YUYUN PRIWAHYUNI; SUHARMADJI SUHARMADJI; RISA AMALIA (LPPM Universitas Abdurrab, 2024)
HIRADC (Hazard Identification, Risk Assessment and Determining Control) is one of the K3 programs in ports that identifies hazards in activities or work processes. Initial interview results showed that there had been an incident during the loading and unloading process at PT Pelindo Dumai which caused minor injuries such as slipping, broken bones and hitting the head. Observation results also found that there were workers who did not use Personal Protective Equipment (PPE). This research aims to determine and analyze the risk of work accidents using the HIRADC method among container loading and unloading workers at PT Pelindo Dumai I in 2023 through the variables of hazard identification, risk assessment and risk control. This type of research is observation with a qualitative analytical approach, and was carried out in July 2023 through document searches, direct observation, and in-depth interviews with 5 informants, namely 1 person from the K3 section as key informant, 3 workers loading and unloading crates packing as the main informant and 1 Supervisor as a supporting informant. The results of the research show that in the three stages/process of container loading and unloading, 25 sources of danger have been identified and the results of the risk assessment obtained a low risk level of 20% with a total of 5 sources of danger, a moderate risk level of 44% with a total of 11 sources of danger and a high risk level of 30 % with a total of 9 sources of danger. The form of hazard control commonly implemented at Pelindo I is the use of PPE. The company should remain consistent in implementing briefings and emphasizing the use of PPE. Apart from that, workers also need to take active relaxation breaks to relax muscle tension due to work.